Analysis of the risk of injury to firefighters based on a functional assessment using the Functional Movement Screen test - Kałużny, Krystian; Kałużna, Anna; Kochański, Bartosz; Wołowiec, Łukasz; Cichosz, Michał; Żukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Introduction. The work of firefighters is at high risk of injury and injury. Firefighters risk their health and their lives each day, carrying help to those in need. In this profession, proper physical fitness and motor preparation are very important. Aim of the study. The aim of the study is to analyze the risk of injury in Voluntary Fire Brigade firefighters on the basis of a functional evaluation using the Functional Movement Screen (FMS). Material and methods. The study was conducted on a group of 25 men - firefighters belonging to the Volunteer Fire Brigade. The functional evaluation was performed using the Functional Movement Screen (FMS). The evaluation consisted of 7 tests assessing functional mobility, stability and coordination. The research was carried out using a device and an FMS test protocol. In addition, each participant completed a survey of their own authorship. Results. Firefighters observed abnormalities in basic motor patterns. The lowest values were obtained in mobility assessments: "Shoulder mobility" - 1.32 points and " Active straight leg raise – ASLR " - 1.52 points. The best result was obtained in test 6 –“Ttrunk stability push up” - 2.04. The average result obtained by firefighters in the FMS test is 11,92. Conclusions. 1. In examined firefighters, abnormalities in basic motor patterns are observed in the FMS test. 2. The risk of injury in FMS surveyed firefighters is very high. 3. The FMS test results correlate with BMI, work experience and age of firefighters. 4. No correlation was found between injuries and injuries and physical activity in firefighters and the FMS test result.